Transferência de equações de chuvas intensas para locais sem registros pluviométricos no estado do Pará - BAHIA, Álon dos Santos (2024)
The generation of rainfall equations is invaluable for urban and highway drainage projects. Hence, there is a critical need to invest in studies enabling the extraction of data on critical rainfall with increased precision. However, despite a considerable amount of data, the state of Pará faces a shortage of precipitation collection stations for some municipalities, or even insufficient and unreliable data. Therefore, the objective is to assess the possibility of using rainfall data from neighboring municipalities to establish synthetic equations that cater to locations lacking such information. For this purpose, 12 collection points in the northeast of the state of Pará were utilized to analyze maximum annual precipitation, averages, and standard deviations. Applying methods such as Gumbel and rainfall disaggregation, rainfall equations were derived and validated using efficiency coefficients (COE). The stations were grouped into three sets of 4 stations each, with one located centrally not exceeding 50 km from the others. Interpolation was then performed using the inverse power-distance method with different possible exponents (ID1, ID2, ID3, ID4, and ID5). Once the synthetic rainfall equation was obtained, quality analysis was conducted through percentage error between the real intensities of the central stations and the synthetic intensities obtained from interpolation. The main results suggest that the method of transferring rainfall equations tends to have a high degree of uncertainty due to the different climatic characteristics present in each municipality. However, it is concluded that it is possible to transfer rainfall equations from adjacent stations, recommending the use of a safety factor of 13 to 18%.